Effect of Plastic Ocean Pollution on Marine Life and Human Health in Brazil - Augusto, Lucas (International Journal of Environmental Sciences, 2024)
Purpose: The aim of the study was to examine effect of plastic ocean pollution on marine life and human health in Brazil. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study found that pervasive presence of plastic debris in Brazil's coastal waters threatens marine ecosystems, leading to entanglement, ingestion, and suffocation of marine species such as seabirds, turtles, and marine mammals. Furthermore, microplastics, resulting from the breakdown of larger plastic items, pose insidious risks to marine life as they are ingested by plankton and subsequently enter the food chain, potentially accumulating in higher trophic levels, including fish consumed by humans. This not only disrupts marine biodiversity but also raises concerns about the safety and quality of seafood, impacting human health and food security in coastal communities. Unique Contribution to Theory, Practice and Policy: Ecological theory, health impact assessment (HIA) theory & environmental justice theory may be used to anchor future studies on Effect of Plastic Ocean Pollution on Marine Life and Human Health in Brazil. Develop and deploy technologies that efficiently remove microplastics and larger debris from marine environments. This includes advancements in filtration systems for water treatment facilities and specialized equipment for collecting debris from ocean surfaces and shorelines. Enforce regulations limiting the production of non-essential single-use plastics, promoting the use of sustainable materials. Policy-makers should consider lifecycle assessments in the approval process of new plastic products.